2017
DOI: 10.14715/cmb/2017.63.2.8
|View full text |Cite
|
Sign up to set email alerts
|

TTY2 genes deletions as genetic risk factor of male infertility

Abstract: Y chromosome has a number of genes that are expressed in testis and have a role in spermatogenesis. TTY2L12A and TTY2L2A are the members of testis transcript Y2 (TTY2) that are Y linked multi-copy gene families, located on Yp11 and Yq11 loci respectively. The aim of this study was to investigate frequency of TTY2L12A and TTY2L2A deletions in azoospermic patients compared with fertile males. This study was performed on 45 infertile males with idiopathic azoospermia without any AZF micro deletions (group A), 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The authors of this paper also concluded the involvement of these genes in spermatogenesis. With a great surprise a more recent publication reported a very low frequency (about 2.2%) microdeletion for both TTY2L2A and TTY2L12A genes in azoospermia patients with no AZFc microdeletion and higher frequency of microdeletions in azoospermia patients with unkown AZF situation [27]. The frequency of reported microdeletions is much lower and in contradiction with our results (Table 1 and Figure 4) and previous report by Yapijakis et al [26].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The authors of this paper also concluded the involvement of these genes in spermatogenesis. With a great surprise a more recent publication reported a very low frequency (about 2.2%) microdeletion for both TTY2L2A and TTY2L12A genes in azoospermia patients with no AZFc microdeletion and higher frequency of microdeletions in azoospermia patients with unkown AZF situation [27]. The frequency of reported microdeletions is much lower and in contradiction with our results (Table 1 and Figure 4) and previous report by Yapijakis et al [26].…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover the deletion in TTY2L12A gene has nothing to do with AZF genes because it is located on the short arm of Y chromosome. Another possibility of lower frequency reported by Shaveisi-Zadeh et al [27] might be related to the studied population with a different ethnicity. However, study of TTY2 gene family is in its early stage.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is important to recognize the genetic basis of infertility to provide better care, as well as an improved prognosis to infertile couples. Several studies have shown how the variation in essential spermatogenesis specific genes led to the impairment of this process and ultimately male infertility (Avenarius et al 2009, Shahid et al 2010, Etem et al 2010, Asadpor et al 2013, Jamshidi et al 2014, Alazami et al 2014, Shaveisi-Zadeh et al 2017, Al-Agha et al 2018, Monsef et al 2018, Akbari et al 2019, Askari, Karamzadeh, et al 2019, Askari, Kordi-Tamandani, et al 2019, Hojati et al 2019, Alimohammadi et al 2020. This section will briefly describe some genes that the deletion or mutation thereof led to impaired male fertility.…”
Section: Genetic Mutationsmentioning
confidence: 99%
“…It is important to recognize the genetic basis of infertility to provide better care, as well as an improved prognosis to infertile couples. Several studies have shown how the variation in essential spermatogenesis specific genes led to the impairment of this process and ultimately male infertility ( Avenarius et al 2009 , Shahid et al 2010 , Etem et al 2010 , Asadpor et al 2013 , Jamshidi et al 2014 , Alazami et al 2014 , Shaveisi-Zadeh et al 2017 , Al-Agha et al 2018 , Monsef et al 2018 , Akbari et al 2019 , Askari, Karamzadeh, et al 2019 , Askari, Kordi-Tamandani, et al 2019 , Hojati et al 2019 , Alimohammadi et al 2020 ). This section will briefly describe some genes that the deletion or mutation thereof led to impaired male fertility.…”
Section: Genetic Mutationsmentioning
confidence: 99%